Kajian Psikoanalisis Henry Murray Pada Tokoh Okkotsu Yuuta Dalam Anime "Jujutsu Kaisen 0" - Fajrun, Muhammad Alfi; Oemiati, Sri (KIRYOKU, 2026)
This research is about the psychoanalytic study of Henry Murray on the character Okkotsu Yuuta in the anime Jujutsu Kaisen 0, using Henry Murray's personology theory. According to Henry Murray, needs are closely related to a person's psychological condition. Henry Murray categorized 20 essential needs related to psychological needs in a person. Using a qualitative descriptive method with a literary approach. Data was collected thru scenes and dialog depicting the psychological aspects of the character Okkotsu Yuuta. The anime Jujutsu Kaisen 0 tells the story of a teenager named Okkotsu Yuuta, who has been haunted by a cursed spirit named Rika since childhood. Yuuta cannot control Rika's cursed spirit, which is attached to him, and it always gets out of control whenever Yuuta is in a dangerous situation. One day, Yuuta met Gojo Satoru, the strongest sorcerer, who invited Yuuta to join Jujutsu High School so that Yuuta could control his powers and also Rika's cursed spirit. This study's goal is to use personology theory to ascertain Okkotsu Yuuta's needs in the anime Jujutsu Kaisen 0. The author found that the character Okkotsu Yuuta has 9 needs that reflect his behavior and emotions when facing inner conflict and his struggle to control the cursed spirit Orimoto Rika. It can be concluded that the character Okkotsu Yuuta has needs for abasement, achievement, affiliation, aggression, counteraction, deference, dominance, nurturance, and rejection.